The Moral Injury of Ineffective Police Leadership: A Perspective - Simmons-Beauchamp, Bobbi; Sharpe, Hillary (Frontiers in Psychology, 2022)
Research suggests that Canadian police officers are exposed to trauma at a greater frequency than the general population. This, combined with other operational stressors such as risk of physical injury, high consequence of error, and strained resources, can leave officers less resilient to organizational stressors. In my experience, a significant and impactful organizational stressors is ineffective leadership, which include leaders who are non-supportive, inconsistent, egocentric, and morally ambiguous. Ineffective leadership in the context of the paramilitary police culture has been recognized as psychologically distressing. Further, moral injury may result when leadership fails to meet officers’ needs, expectations, and values. Ineffective leadership and resulting moral injury is an understudied area in the literature. This review will help provide a comprehensive context of policing and the impact of ineffective leadership on police mental health.